Photoelectrochemical hole injection revealed in polyoxotitanate nanocrystals functionalized with organic adsorbates - Negre, Christian Francisco Andres (2014)
We find that crystallographically resolved Ti17O24(OPri)20 nanoparticles, functionalized by covalent attachment of 4-nitrophenyl-acetylacetonate or coumarin 343 adsorbates, exhibit hole injection into surface states when photoexcited with visible light (λ = 400–680 nm). Our findings are supported by photoelectrochemical measurements, EPR spectroscopy, and quantum dynamics simulations of interfacial charge transfer. The underlying mechanism is consistent with measurements of photocathodic currents generated with visible light for thin layers of functionalized polyoxotitanate nanocrystals deposited on FTO working electrodes. The reported experimental and theoretical analysis demonstrates for the first time the feasibility of p-type sensitization of TiO2 solely based on covalent binding of organic adsorbates.